λOpt: Learn to Regularize Recommender Models in Finer Levels - Chen, Yihong; Chen, Bei; He, Xiangnan; Gao, Chen; Li, Yong; Lou, Jian-Guang; Wang, Yue (SigKDD19, 2019)
Recommendation models mainly deal with categorical variables, such as user/item ID and attributes. Besides the high-cardinality issue, the interactions among such categorical variables are usually long-tailed, with the head made up of highly frequent values and a long tail of rare ones. This phenomenon results in the data sparsity issue, making it essential to regularize the models to ensure generalization. The common practice is to employ grid search to manually tune regularization hyperparameters based on the validation data. However, it requires non-trivial efforts and large computation resources to search the whole candidate space; even so, it may not lead to the optimal choice, for which different parameters should have different regularization strengths. In this paper, we propose a hyperparameter optimization method, λOpt1, which automatically and adaptively enforces regularization during training. Specifically ,i tupdate sth eregularizatio ncoefficients based on the performance of validation data. With λOpt, the notorious tuning of regularization hyperparameters can be avoided; more importantly, it allows fine-grained regularization (i.e .each parameter can have an individualized regularization coefficient), leading to better generalized models. We show how to employ λOpt on matrix factorization, a classical model that is representative of a large family of recommender models. Extensive experiments on two public benchmarks demonstrate the superiority of our method in boosting the performance of top-K recommendation.